2013
DOI: 10.3171/2013.4.peds12539
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional benefits of selective dorsal rhizotomy for spastic cerebral palsy

Abstract: Object Large-scale natural history studies of gross motor development have shown that children with spastic cerebral palsy (CP) plateau during childhood and actually decline through adolescence. Selective dorsal rhizotomy (SDR) is a well-recognized treatment for spastic CP, but little is known about long-term outcomes of this treatment. The purpose of this study was to assess the durability of functional outcomes in a large number of patients through adolescence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 25 publications
6
81
2
6
Order By: Relevance
“…Nordmark et al and Josenby et al found that patients also had improvements in their Paediatric Evaluation of Disability Inventory (PEDI) scores, notably in the functional skills and mobility domains (27,31). Dudley et al found that these gains persisted to 15 years post-SDR (29). The multidimensional benefits of SDR were evident from the PEDI score results, where significant gains in self-care and mobility persisted through to early adulthood.…”
Section: Outcome Of Sdrmentioning
confidence: 70%
See 1 more Smart Citation
“…Nordmark et al and Josenby et al found that patients also had improvements in their Paediatric Evaluation of Disability Inventory (PEDI) scores, notably in the functional skills and mobility domains (27,31). Dudley et al found that these gains persisted to 15 years post-SDR (29). The multidimensional benefits of SDR were evident from the PEDI score results, where significant gains in self-care and mobility persisted through to early adulthood.…”
Section: Outcome Of Sdrmentioning
confidence: 70%
“…The multidimensional benefits of SDR were evident from the PEDI score results, where significant gains in self-care and mobility persisted through to early adulthood. Moreover, SDR patients in this study compared with children who did not undergo SDR had a significant reduction in the need for further orthopedic intervention (29). Tedroff et al on the other hand found that, while spasticity was significantly reduced by SDR at 15-20 years post-SDR, contractures were not prevented and long-term functioning was not improved (28).…”
Section: Outcome Of Sdrmentioning
confidence: 89%
“…In a recent study [11] involving a large number of CP children (n=102) with spastic diplegia, the authors assessed the long-term effects of SDR 1, 5, 10 and 15 years after the operation. Of the 102 children, 57 were assessed at 10 years and 14 were assessed at 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent large nonrandomized studies have found similar functional improvements that persist at up to 26 years postoperatively. 4,7,18,36 The presumed mechanism by which SDR alleviates spasticity is by modulation of afferent inputs to lower motor neurons to compensate for a loss of upper motor neuron regulation, although the details of this mechanism are poorly understood. 15 The most common imaging finding associated with CP is periventricular leukomalacia, which is associated with necrosis of the periventricular and subcortical white matter.…”
Section: Discussionmentioning
confidence: 99%